Highly stable multicrown heterostructures of type-II nanoplatelets for ultralow threshold optical gain - Dede, Didem (2020)
Solution-processed type-II quantum wells exhibit outstanding optical properties, which make them promising candidates for light-generating applications including lasers and LEDs. However, they may suffer from poor colloidal stability under ambient conditions and show strong tendency to assemble into face-to-face stacks. In this work, to resolve the colloidal stability and uncontrolled stacking issues, we proposed and synthesized CdSe/CdSe 1-x Te x /CdS core/multicrown heteronanoplatelets (NPLs), controlling the amount of Te up to 50% in the crown without changing their thicknesses, which significantly increases their colloidal and photostability under ambient conditions and at the same time preserving their attractive optical properties. Confirming the final lateral growth of CdS sidewalls with X-ray photoelectron spectroscopy, energy-dispersive analysis, and photoelectron excitation spectroscopy, we found that the successful coating of this CdS crown around the periphery of conventional type-II NPLs prevents the unwanted formation of needle-like stacks, which results in reduction of the undesired scattering losses in thin-film samples of these NPLs. Owing to highly efficient exciton funneling from the outmost CdS crown accompanied by the reduced scattering and very low waveguide loss coefficient (18 cm -1 ), ultralow optical gain thresholds of multicrown type-II NPLs were achieved to be as low as 4.15 μJ/cm 2 and 2.48 mJ/cm 2 under one- and two-photon absorption pumping, respectively. These findings indicate that the strategy of using engineered advanced heterostructures of nanoplatelets provides solutions for improved colloidal stability and enables enhanced photonic performance.